2008
DOI: 10.1002/arch.20279
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic castration of Plutella xylostella larvae induced by polydnaviruses and venom of Cotesia vestalis and Diadegma semiclausum

Abstract: In the present study, we used gamma-ray to irradiate the female parasitoids to make wasp eggs infertile, resulting in pseudoparasitization, which allowed the analysis of maternal secretions such as polydnaviruses (PDVs) and venom in the absence of larval secretions or teratocytes by the growing parasitoids. We then investigated the spermatogenesis and components of testicular proteins of male Plutella xylostella larvae pseudoparasitized by two endoparasitoids (Cotesia vestalis and Diadegma semiclausum). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…[21][22][23] Several studies have shown that parasitic wasps have significant effects on host metabolism and development through interruption of host gene transcription, immune pathways, nutrition, and endocrine systems, and even regulate miRNA levels. 18,[24][25][26][27][28][29] Therefore, endoparasitoid wasps provide ideal biological tools to study the basic mechanisms underlying insect immune responses due to their profound impact on the host immune system.…”
Section: Conserved Microrna Mir-8 Blocks Activation Of the Toll Pathwmentioning
confidence: 99%
“…[21][22][23] Several studies have shown that parasitic wasps have significant effects on host metabolism and development through interruption of host gene transcription, immune pathways, nutrition, and endocrine systems, and even regulate miRNA levels. 18,[24][25][26][27][28][29] Therefore, endoparasitoid wasps provide ideal biological tools to study the basic mechanisms underlying insect immune responses due to their profound impact on the host immune system.…”
Section: Conserved Microrna Mir-8 Blocks Activation Of the Toll Pathwmentioning
confidence: 99%
“…10 A number of biophysical analyses specifically looking at the structure of model antigens bound to aluminum based hydrated gels, have revealed none or subtle effects upon the bound protein. [11][12][13][14][15][16] Even though alum adjuvantation is not expected to affect the properties of Sm-Tsp-2, future studies will be able to address and document that this indeed is the case.…”
Section: Introductionmentioning
confidence: 99%
“…For pseudo-parasitization, C. vestalis adult females were exposed to a Cesium 137 source at a dose of 120 Gy for 1 h51. These gamma-irradiated females were then used to pseudo-parasitize hosts while other hosts were parasitized by normal (non-irradiated) females.…”
Section: Methodsmentioning
confidence: 99%